Use and appreciation of Mycenaean pottery in the Levant, Cyprus and Italy (1600-1200 BC) - Wijngaarden, Gert Jan van (Amsterdam archaeological studies, 2002)
New insights into the significance of context through this meticulous interpretation of findings of Mycenaean pottery.